Runge pairs of Φ-like domains - HAMADA, Hidetaka; IANCU, Mihai; KOHR, †Gabriela (Studia Universitatis Babeș-Bolyai Mathematica, 2022)
We prove that if E ⊆ Cn is a Φ-like domain and D ⊆ E is a Φ-like domain, then (D; E) is a Runge pair. Certain applications, examples and questions are also provided. Mathematics Subject Classification (2010): 32E30, 30C45, 32H99. Received 18 January 2022; Accepted 20 January 2022.